Prevalence of intestinal parasitic infections and associated factors among street children in Jimma town; south West Ethiopia in 2019: a cross sectional study - Sabit Zenu; Eshetu Alemayehu; Kifle Woldemichael (BMC, 2019)
Abstract Background Street child is any child whose age is less than 18 years for whom the street has become his or her habitual abode and/or source of livelihood, is inadequately protected, supervised or directed by responsible adults. In Ethiopia the health problems of street children are given poor attention in research. This problem is pronounced when it comes to intestinal parasitic infections, making it difficult to design appropriate interventions targeting this segment of population. The aim of this study was to assess the prevalence of intestinal parasitic infections and associated factors among street children in Jimma town in the year 2019. Methods Community based cross sectional study was employed. Complete enumeration was used to include 312 street children. Pretested questionnaire was used to collect the data. Data was entered to Epidata version 3.1 and exported to SPSS version 20. Stool samples were examined by wet mount and formalin ether concentration techniques. Bivariable and multivariable logistic regression was used to identify factors associated with intestinal parasitic infection. Significance of association was decided by using the 95% confidence interval of AOR and P-value of ≤0.05 in the multivariable model. Result A total of 312 children of the street were involved in the study making the response rate 96.2%. The prevalence of intestinal parasitic infection was 66.7%. Untrimmed finger nails AOR = 2.03;95%CI (1.02-4.06), eating street food AOR = 2.24;95% CI (1.04-5.02), practice of swimming in unprotected water bodies AOR = 2.5; 95% CI (1.24-5.04), not wearing shoes at the time of data collection AOR = 3.8;95% CI (1.8-8.2) and lacking knowledge of way of transmission of intestinal parasites AOR = 2.5; 95% CI (1.25-5.0) were significantly associated with parasitic infections. Conclusions The prevalence of intestinal parasitic infections among street children in the study area was high and require integrated interventions to avert the problem. Several factors were also found to be associated with intestinal parasitic infections. Measures has to be taken to curb the problem by including them in mass drug administration and targeted health education towards identified factors.